ANALISIS KRITERIA RADIOGRAFI OS PATELLA DAN PATELOFEMORAL JOINT DENGAN PROYEKSI SKYLINE METODE HUNGSTON DAN SETTEGAST: Radiologi - Mahfud, Mahfud (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2023)
Background: the problem in radiographic examination of Os Patella and Patellofemoral joint is the limitation in showing the picture of Os Patella from the infero-superior aspect which is free from superposition with other surrounding organs and also to show the distance between Os Patella and Condylus Femoralis Joint. Objective: to analyze the criteria for the results of the Os Patella and Patellofemoral joint examination in providing optimal and informative results according to diagnostic needs. Methods: This study used a descriptive qualitative design, with a sample of 10 patients. Research Results: radiographic images of the Hungston method in the prone patient position and knee flexed to form 550 with 450 cranially ray direction can provide informative results in the examination of Os Patella and Patellofemoral Joint because it can provide optimal anatomical image criteria and open Patellofemoral Joint Interspace than the Settegast method. Conclusion: the Hungston method is able to show optimal and informative image results for use in examining the Os Patella and Patellofemoral Joint Skyline projection.